2020
DOI: 10.3389/fnins.2019.01428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Functions of Two Amazonian Populations: Possible Consequences of Different Mercury Exposure

Abstract: The present study investigated the visual perimetry and color vision of two Amazonian populations differently exposed to mercury. Ten riverines environmentally exposed to mercury by fish eating and 34 gold-miners occupationally exposed to mercury vapor. The visual perimetry was estimated using the Förster perimeter and the color vision was evaluated using a computerized version of Farnsworth-Munsell test. Riverine and gold-miners' hair mercury concentrations were quantified. Mercury hair concentration of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 34 publications
1
43
0
2
Order By: Relevance
“…Nonetheless, when we focus only on research conducted in the Amazon region, we observe that most of these studies indicate that exposure to MeHg may be responsible for neurological alterations in adult individuals [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In this region, the mercury levels detected in exposure biomarkers can be up to 10-fold higher than the limits recommended by health agencies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, when we focus only on research conducted in the Amazon region, we observe that most of these studies indicate that exposure to MeHg may be responsible for neurological alterations in adult individuals [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In this region, the mercury levels detected in exposure biomarkers can be up to 10-fold higher than the limits recommended by health agencies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, research conducted in the Amazon region identified adult individuals with neurological abnormalities probably associated with the consumption of contaminated fish. In those individuals, levels of methylmercury in hair samples varied between 10 and 20 µg/g [ 12 , 13 , 14 , 15 , 16 , 17 ]. Similar findings were reported in riparian populations in Bolivia and Suriname [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies regarding the effect of mercury on adult's health revealed emotional changes, such as depression and aggressiveness, motor problems [59], and changes in the visual field [60]. Furthermore, some studies have demonstrated an association between MeHg exposure with the development of neurodegenerative diseases such as Alzheimer's and Parkinson's disease [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…provides the main route of human exposure to this persistent environmental contaminant [27]. Ingested methylmercury is rapidly absorbed by the human gastrointestinal tract, principally affecting the central nervous and cardiovascular systems [28][29][30]. This mercurial form is especially harmful to pregnant women because the fetal brain is more sensitive to the action of methylmercury, causing many neurodevelopment problems to occur, including mental retardation, learning delays, visual and auditory alterations, and other harmful effects [31][32][33].…”
Section: Introductionmentioning
confidence: 99%